Analisis Maqāṣid Al-Syarī‘Ah Terhadap Pertimbangan Hakim Dalam Pemberian Izin Poligami Di Pengadilan Agama Kota Bima - Wahyu Saputra; Muh. Yunan Putra; Hikmah (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study aims to analyze the judges' considerations in granting permission for polygamy at the Religious Court of Bima City. Polygamy in Islamic law is permitted under certain conditions; however, its implementation in the context of Indonesian positive law is restricted by Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). The focus of this research is on how judges interpret and apply these conditions, particularly in relation to justice, the husband's capability, and the condition of the first wife. This study employs a normative juridical approach with qualitative analysis of court decisions related to polygamy permits. The results show that judges at the Religious Court of Bima City carefully consider aspects of justice and the welfare of wives and children when ruling on polygamy cases, and they rigorously assess the evidence presented by applicants. Therefore, the judges’ considerations are based not only on normative regulations but also on the principles of justice and the protection of women's rights. These findings reflect the judiciary’s caution in handling polygamy cases as a form of protection for the institution of the family.